EFEKTIVITAS PERTUMBUHAN DYSOXYLUM MOLLISSIMUM BLUME PADA TINGKAT PANCANG DI LAHAN KONDISI TERBUKA DAN TERNAUNGI - Efratenta Katherina Depari; P.B.A. Nugroho; Saprinurdin - (Jurnal Hutan Tropis, 2021)
Kayu Bawang (Dysoxylum mollissimum Blume) has long been used for carpentry and furniture. However, the cultivation of this plant has not been done well. The purpose of this research was to determine the effectiveness of Kayu bawang growth to sapling stage in open and shaded conditions. Planting Kayu bawang as object of the research has been executed since March 24, 2016 on open and shaded condition. The observed variables included diameter, height and leaf chlorophyll of the plant. The measurements were made up to 2-year-old plants.  The effectiveness of Kayu bawang growth in open and shaded conditions was tested using the t-test. The results showed that the diameter of Kayu bawang in open condition was 8.91±1.87 cm and in shaded conditions was 5.42±1.67 cm. The height of Kayu bawang in open conditions was 433±70 cm and in shaded condition was 283±100 cm. The chlorophyll of Kayu bawang in open condition was 57.6±5.3 and in shaded condition was 53.8±4.0. Statistical analysis for the three variables showed that the growth of Kayu bawang at the sapling stage in open conditions was more effective than in shaded conditions.